2022
DOI: 10.14366/usg.21254
|View full text |Cite
|
Sign up to set email alerts
|

Can the ultrasound echogenicity of normal parotid and submandibular glands be used as a reference standard for normal thyroid echogenicity?

Abstract: Purpose: This study aimed to determine whether the normal parotid gland (PG) and submandibular gland (SMG) can be used as reference standards for normal thyroid echogenicity.Methods: In total, 1,302 consecutive patients with normal salivary glands were included in this study. The echogenicity of the SMG and PG was assessed during real-time ultrasound examinations, and the glands were categorized as hyperechogenic, isoechogenic, and hypoechogenic relative to the thyroid parenchyma in patients without diffuse th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Furthermore, it can be assumed that not all researchers distinguish between isoechogenicity and slight hypoechogenicity, thereby affecting their findings and conclusions. This assumption is based on the attempts of specialists to compare thyroid echogenicity with the frequent slight hypoechogenicity of salivary glands ( 20 ), as well as their insufficient experience in visually evaluating a grey scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it can be assumed that not all researchers distinguish between isoechogenicity and slight hypoechogenicity, thereby affecting their findings and conclusions. This assumption is based on the attempts of specialists to compare thyroid echogenicity with the frequent slight hypoechogenicity of salivary glands ( 20 ), as well as their insufficient experience in visually evaluating a grey scale.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, sonologists can visually differentiate between lower and higher hypoechogenicity at the same basic settings of the device. Furthermore, they can assess the echogenicity of the thyroid gland not only from memory and personal perception but also by comparing it with that of the parotid gland, if necessary ( 20 ). During US examination, human vision can distinguish isoechogenicity ( Figure 1A ) and the three variants of hypoechogenicity as follows: slight, moderate (average) and significant ( Figure 1B-1D ).…”
Section: Sonographic Variants Of Thyroid Hypoechogenicitymentioning
confidence: 99%
“…Interestingly, thyroid viscosity found by our study and submandibular gland viscosity values found by the above-mentioned study are highly similar. The echogenicity of the SMG and PG has previously been considered as reference for the echogenicity of normal thyroid tissue [ 27 ], but elasticity or viscosity values were not yet compared.…”
Section: Discussionmentioning
confidence: 99%
“…- Initially in B-mode US, the thyroid volume and echogenicity were evaluated. The thyroid volume was calculated in each case by measuring for each lobe the anteroposterior, transverse, and longitudinal diameter and calculated by the machine using the ellipsoid volume formula; the echogenicity was qualitatively assessed by the US operator as isoechoic (0), mildly (1) or intensely hypoechoic (2) (compared to salivary gland aspect) ( 40 );…”
Section: Methodsmentioning
confidence: 99%